The Effect of Drug Variety And Brand on Patient Recovery Value (A Study at Sentot Alibasyah Polyclinic Yakes Telkom Bandung) - Deden Romansyah; Feby Febrian; Agus Mulyana (International Journal of Psychology and Health Science, 2023)
Deden Romansyah, 2022. The effect of Variations and Barnds of Drug on the Patients Healing value a Study on Poliklinik Sentot Alibasyah Yakes Telkom Bandung. Under guidance of Prof. Dr. Hj. Ai Komariah, Ir., MS., CHRA and Dr. Hj. Winna Roswinna, SE., MM., CPM. This study aims to test whether there is an effect between variations and brands of drugs on the patient's healing value.The subjects of this study were patients at the Sentot Ali Basyah Polyclinic, Yayasn Kesehatan Telkom Bandung. It is important to do this to determine the effectiveness of providing variations and brands of drugs that have been carried out in the form of the Telkom Drug List. This study uses a survey research method with the type of research used is research to test hypotheses by collecting data in the field or verification research using descriptive analysis. The number of variations and brands of drugs may affect the patient's health value.